Media Sosial Sebagai Sarana Promosi dan Komunikasi Objek Wisata - Tisa, Mutia (FDIK IAIN Padangsidimpuan, 2019)
The development and progress of a tourist attraction are very much determined by the level of promotion and communication strategies carried out by all tourism actors, without good promotional activities and effective communication it will be impossible to obtain information about tourism in an area to the wider community. In the developing digital era, social media is one of the most suitable media to be used by all stakeholders and the wider community in promoting tourism objects owned by each region, on the grounds that social media is easier to use, cost-effective and effective in tourism marketing.